Productivity, competition and economics of intercropping legumes in finger millet (Eleusine coracana) at different fertility levels - MAITRA, S; GHOSH, D C; SOUNDA, G; JANA, P K; ROY, D K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1994 - 95 at Birbhum (West Bengal) to study the performances of inter croppinglegumes in finger millet at different fertility levels, The results indicated that intercropping red gram (Cajanus cajan L.Millsp.) and groundnut (Arachis /zypogaea L.) in finger millet (Eleusine coracana L. Gaertn.) gave higher total grain andstraw yield compared to the sole cropping of finger millet under rainfed condition of upland (Ultisols) in lateritic belt ofWest Bengal. Intercropping pigconpea in finger millet increased land equivalent ratio, aggressivity, relative crowding coefficient and area time equivalent ratio. Legumes were more aggressive in intercropping system and tended to havedepressing effect on finger millet. Intercropping of finger millet + pigeonpea and finger millet + groundnut showed higher net return and benefit: cost ratio. Application of 60-13.3-25 kg N-P-K/ha recorded maximum productivity and thehighest net refurn followed by the application of 30-6.7-12.5 kg N-P-K/ha. However, the highest benefit/cost ratio wasobtained from application of 30-6. 7-12.5 kg N-P-K/ha.